Alimentação de recém-nascidos e lactentes a termo e prematuros atendidos em um hospital escola - Yagi, Rosicler Garcia Rodrigues (2005)
Brazilian government policy of public health aims to promote and support breastfeeding; consequently reducing the infant mortality as well as improving the children´s quality of life. The objectives of this study were: a) to observe the diet of premature and full-term babies aged under two years, assessing the breastfeeding indicators of the World Health Organization (WHO): exclusive breastfeeding, predominant breastfeeding, complementary proper foods, continued breastfeeding and milk bottle feeding; b) to compare standardized diets among premature and full-term newborns. Casuistics: Two hundred of mothers of newborns and infants participated the study. They were divided into four groups (50 each): Group I (< 4 months); Group II ( between 6 and <10 months); Group III ( between 12 and < 16 months); Group IV ( between 20 and <24 months). Method: At first the project was approved by the Ethics Committee of Research. Afterwards, before the routinely consulting, the mothers answered a questionnaire based on a methodology standardized by WHO about information of diet during the last 24 hours. Results: The majority of mothers was adult (lesser than 20% of adolescents), able to read and write (97%; IC:93 to 99%), living with a partner (estimative of 79.5%; IC:73 to 85%), minority worked outside (27%; IC:21 to 34%). Average of 70.5% (IC:64 to 77%) of cesarean labor and 50.5% (IC:43 to 57%) of premature labor. The minority performed the first breastfeeding in the labor room (estimative of 18%; IC:13 to 25%). In Group I, the rate of exclusive breastfeeding was 40% (IC:26 to 55%), and predominant breastfeeding 28% (IC:16 to 42%). In Group II, the rate of breastfeeding with complementary proper foods was 46% (IC:32 to 61%). In Group III, the rate of continued breastfeeding up to one year was 30% (IC:18 to 45%); and in Group IV, the rate of continued breastfeeding up to two years was 32% (IC:20 to 47%). The rate of milk bottle feeding for babies under one year was 57% (IC:47 to 67%). Conclusions: The characteristics of the groups of mothers and babies were almost homogeneous, both have been following partially the facilitator routines of breastfeeding. As the age of babies increased, breastfeeding diminished, with the early introduction of liquids and complementary diet. The standardized diet of full-term and premature babies was similar.